DAILYMOTION APPLICATION AS TEACHING MEDIA TO INCREASE STUDENTS’ LISTENING SKILL - Vetricia Emilia; Andi Hamzah Fansury; Muliati Muliati (Publikasi dan UKI Press UKI Toraja., 2023)
This study aimed to know the effect of the flipped classroom model on students' writing skill in class XI SMA Negeri 18 Makassar. This study focused on pre-experimental research one group pre-test and post-test. The population in this study were students of class XI SMAN 18 Makassar. The writer took 270 students as the population. Random sampling technique was used to take one class as the research sample, totaling 30 students. Data obtained from writing test. The results of this study used inferential analysis of the t-test by SPSS v.16, which showed a significant effect on the students’ mean score writing skill between the pretest and post-test. The mean score of the students’ writing enhanced from 52.33 in the pretest to 82.03 in the posttest. The significance value calculated 0.000 is smaller than 0.05 (P-value = 0.000 < 0.05). This study aims to determine whether the use of the Dailymotion Application as a learning media can improve students listening skill of eleven grade at SMA Negeri 4 Makassar. This study uses a pre-experimental research method in one class pre-test and post-test. The population of this research is the eleven grade students of SMA Negeri 4 Makassar in the academic year 2022/2023. The number of samples 30 students from class XI-8. Data obtained from listening test. The results were analyzed using the inferential t-test of the SPSS 22.0 application. And after doing research, the researcher concludes that the use of the Dailymotion Application as a learning media can improve students' listening skill. This can be proven by obtaining scores based on the students' pretest and post-test. The mean score increased from 60.83 on the pre-test to 88.30 on the post-test. This shows that the H? hypothesis is accepted and of course the H? hypothesis is rejected. This means that the Dailymotion application can improve the listening skill of students in the eleven grade of SMA Negeri 4 Makassar